IMPLEMENTASI BANTUAN LANGSUNG TUNAI DANA DESA (BLT DD) DI DESA SUMORAME KECAMATAN CANDI - Nur Arivah Endah Prastiwi; Hendra Sukmana (Halu Oleo University, 2025)
This research aims to describe and analyze the implementation of Village Fund Cash Assistance (BLT-DD) in Sumorame Village, Candi Sub-district. This study uses a descriptive qualitative approach, with data gathered from interviews, observations, and literature reviews. The research focuses on how BLT-DD is implemented in Sumorame Village. The findings highlight several key aspects of the policy's execution. First, effective communication through socialization during the Special Village Deliberation (Musyawarah Desa Khusus) helped the residents clearly understand the eligibility criteria and distribution mechanism. Second, well-qualified human resources were involved, with staff knowledgeable about the procedures and working together to ensure the aid was distributed properly. The budgeting process, which started with the village deliberation and was authorized through the Village Budget (APBDes), followed government guidelines, with a maximum of 25% of the Village Fund allocated for BLT DD. Third, there was a strong commitment from implementers, as they collaborated with various parties to ensure timely distribution. Lastly, a well-organized bureaucratic structure with clear Standard Operating Procedures (SOPs) supported the smooth implementation of the policy. Although there were some challenges in managing recipient data, overall, the implementation of BLT-DD in Sumorame Village was successful in utilizing resources effectively and achieving the goal of assisting the community.